Harmonisasi Kewenangan Mengadili Antara Pengadilan Tindak Pidana Korupsi dan Pengadilan Tata Usaha Negara Dalam Menilai Ada Atau Tidaknya Penyalahgunaan Kewenangan - Baseno, Ongky Ramadhan; Ahmad, Muh. Jufri (Media Hukum Indonesia (MHI), 2024)
The existence of the UUAP has given the PTUN attribution of authority in receiving, examining and deciding whether or not there are elements of abuse of authority in a decision and/or action from a government official. Based on this, several problems emerged related to the authority to adjudicate the PTUN and also the authority to adjudicate the Corruption Court, where previously the authority to adjudicate criminal acts of corruption was the primary function of the Corruption Court. After the birth of Perma No. 4 of 2015, PTUN can accept requests whether or not there is abuse of authority. Fundamental to this, there is a problem formulation used, namely as follows: Can officials who are accused of abuse of authority submit an application to the PTUN in accordance with Perma No. 4/2015? The research method used in writing this thesis is a legal research method and uses a conceptual approach, a legal approach. The object of the request for testing in Article 2 paragraph (2) of Perma 4/2015 uses the phrase "after the results of APIP supervision". In terms of the principles of forming good legislative regulations, this formulation is contrary to the principle of clarity of formulation, because the choice of words or terms used gives rise to various kinds of interpretations. Because, the interpretation can be in the form of: (a) LHP APIP decision; (b) follow-up decisions from the LHP issued by authorized officials; (c) LHP APIP follow-up decisions issued by APH; and (d) the applicant's own decision.